The prevalence of anxiety among medical students - Mohd Sidik, Sherina; Gyanchand Rampal, Lekhraj Rampal; Kaneson, Nadarajan (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2005)
This study was conducted to determine the prevalence of anxiety among medical student at local university in Malaysia and to identify its associated factors. Methods: a cross-sectional study design was used. Three hundred and ninety six medical students at a local university in Malaysia were included in the study, a pre tested, modified, elf administered Beck Anxiety inventory (BAI) was used to screen for anxiety, Results: three hundred and ninety six out of 414 medical students participated (response rate 95.75). 38.45 of the medicals students were found to have anxiety. Conclusion: The overall prevalence of anxiety among medicals students was high (38.4%). Factors found to be significantly associated with anxiety were gender, perceived level of pressure, year of study in medical school, ethnicity and depression )p,0.05)